Effectiveness of Room Boy's performance in Optimizing Room Service Quality at Artotel Hotel Semarang - Permana, Aditya Agung; Krisnawati Setyaningrum Nugrahen; Mistriani, Nina (PT. Banjarese Pacific Indonesia, 2024)
This study is intended to analyze the eﬀectiveness of managing room boy works directly on optimizing the quality of room service in Artotel Hotel Semarang. In the hotel industry, quality room service is characterized as one of the critical factors that has an impact on the level of guest satisfaction and customer loyalty. The room boys are an integral part of the hotel operations and are responsible for ensuring rooms are clean, tidy, and ready so that guests always feel comfortable and accommodated in a beautiful environment. This study employs the qualitative approach of research types using data collection techniques through direct observation, in-depth interviews with room boys and hotel management as well as guest satisfaction surveys. The findings indicate that the good work performance of the room boy has a great inﬂuence on providing high-quality robust service. It was concluded that trained room boys have high motivation and when they are provided with proper tools and materials good room service is possible. In this case, the room boy's performance can be enhanced by hotel management to ensure that they provide frequent training, and work facilities as well as proper and fair assessment and appreciation to the subordinates. It is the ﬁnding of this research that room boy work optimization can be done through training, management, and productivity-oriented assessments.